The building envelope : applications of new technology cladding - Brookes, Alan, 1939- (Butterworth Architecture, 1990)
The Building Envelope: Applications of New Technology Cladding provides an introduction to the state of the art in cladding systems. The goal is to show a precedent, and thus imbue confidence in architects so that they can approach a manufacturer with a reasonable working knowledge of what is feasible. This book contains 33 case studies of buildings which incorporate newer forms of construction technology. The buildings discussed include the Bandstand at Haarlem, Holland; Benthem and Crouwel's House at Almere, a town near Amsterdam, Holland; the Burrell Gallery in Glasgow, Scotland; Clarke Asc.